Industrial biofouling : occurrence and control - Bott, T. R. (Theodore Reginald), 1927- (Elsevier, 2010)
Industrial Biofouling discusses the the challenges--and to a lesser extent, the benefits--of biofilms on industrial processing surfaces. It addresses the operating problems caused by establishment and growth of microorganisms, thereby enabling effective equipment design and operation that minimizes biofouling. Discusses the chemical and physical control of biofilm growth, with coverage of dosing techniques, equipment cleaning, and cost management Presents methods for monitoring and evaluating the effectiveness of control techniques Incorporates explicit figures and diagrams to aid in understanding.